Acromioclavicular Joint Augmentation Poststabilization Using Knotless Anchors - Nasri H. Zreik, M.B., Ch.B.(Hons.), B.Sc.(Hons.), M.Sc.(Res.), P.G.Cert.(Med. Ed.), F.R.C.S.(Orth.), F.E.B.O.T., F.H.E.A.; Magnus Arnander, M.Sc., F.R.C.S.(Orth.), Dip.Hand. Surg.; Eyiyemi Pearse, B.M., B.Ch.(Oxon.), B.A.(Hons.), M.A.(Oxon.), F.R.C.S.(Orth.); Duncan Tennent, B.Sc.(Hons.), F.R.C.S.(Orth.), Pg.Cert.(Med.Ed.), M.Acad.M.Ed., F.F.S.T.Ed. (Arthroscopy Techniques)
Acromioclavicular joint injuries are most commonly present in men aged between 20 and 40 years. Management of high-grade injuries involves reconstruction of the coracoclavicular ligaments, addressing the coronal instability of the joint. More than 100 techniques are described to manage these injuries. Reconstruction of the joint in this plane may achieve an excellent radiographic reduction; however, it may remain unstable in an anteroposterior direction (sagittal instability), resulting in ongoing symptoms. We present a 2-anchor technique that augments the acromioclavicular joint after reconstruction. It is low-profile, reproducible with on-shelf available equipment, and provides additional sagittal stability that may reduce the risk of ongoing postrecovery symptoms.